2016
DOI: 10.1063/1.4948785
|View full text |Cite
|
Sign up to set email alerts
|

A Landau-de Gennes theory for hard colloidal rods: Defects and tactoids

Abstract: We construct a phenomenological Landau-de Gennes theory for hard colloidal rods by performing an order parameter expansion of the chemical-potential dependent grand potential. By fitting the coefficients to known results of Onsager theory, we are not only able to describe the isotropic-nematic phase transition as function of density, including the well-known density jump, but also the isotropic-nematic planar interface. The resulting theory is applied in calculations of the isotropic core size in a radial hedg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 74 publications
2
42
0
Order By: Relevance
“…These nematic droplets have characteristic shapes that have already been the subject of several theoretical studies [2][3][4][5][6][7][8] and experiments on systems such as vanadium pentoxide (V 2 O 5 ) [2,9], carbon nanotubes [10,11], rodlike viruses [12,13], F-actin in cells [14], chromonic liquid crystals [15], and cellulose nano-crystals [16][17][18]. These investigations showed that the typical tactoid shapes, for example the so-called spindle-like shape with a bipolar director field (see the right inset in Fig.…”
Section: Introductionmentioning
confidence: 91%
“…These nematic droplets have characteristic shapes that have already been the subject of several theoretical studies [2][3][4][5][6][7][8] and experiments on systems such as vanadium pentoxide (V 2 O 5 ) [2,9], carbon nanotubes [10,11], rodlike viruses [12,13], F-actin in cells [14], chromonic liquid crystals [15], and cellulose nano-crystals [16][17][18]. These investigations showed that the typical tactoid shapes, for example the so-called spindle-like shape with a bipolar director field (see the right inset in Fig.…”
Section: Introductionmentioning
confidence: 91%
“…As shown in Ref. [80] and as we will review in Chapter 4, the expansion (1.11) can describe a first-order I-N transition at chemical potential µ IN . As shown in Fig.…”
Section: Landau-de Gennes Theory For Uniaxial Nematicsmentioning
confidence: 91%
“…As recently shown in Ref. [80], to deal with lyotropic systems it is convenient to set up a Landau expansion of the chemical-potential dependent grand potential Ω rather than of the temperature-dependent Helmholtz (or Gibbs) free energy F. By using Ω, the density dependence will naturally be encoded through the relation ∂(Ω/V )/∂µ| V,T = −ρ, with V the volume of the system and ρ the average density. In particular, in Ref.…”
Section: Landau-de Gennes Theory For Uniaxial Nematicsmentioning
confidence: 99%
See 2 more Smart Citations